ANALISIS PENERAPAN SISTEM OPERASI LINUX DAN MIKROTIK TERHADAP KECEPATAN AKSES (STUDI KASUS WARNET KOTA PALEMBANG) - Panjaitan, Febriyanti; Ulfa, Maria (JURNAL ILMIAH MATRIK, 2016)
Abstract: In the advancement of information technology, namely the Internet, and web hosting as well as internet warnet or better known term cafe is increasingly widespread and growing every year. Many warnet that exist in the city of Palembang just a few warnet that use Linux operating system and operating system Mikrotik, this is due to the cafe just rely on the facilities provided without considering connections and needs of each client. The research will be carried out analysis implementation server operating system that has been used several internet cafÃ©s in the city of Palembang to see speed internet access. With the research is expected to see how much influence the linux operating system and a proxy server for internet access speeds at every cafe that uses server operating system and taken consideration for each Internet cafe to use Linux operating system and a proxy server in managing the Internet network. Keywords: Public Internet, Linux Operating System, Operating System Mikrotik